An Overview of Teaching Listening in Islamic Tertiary Level of Education - Saehu, Andang (Jurnal Pendidikan Islam, 2016)
The ultimate aim of this paper is to depict listening activities in teaching Basic Listening designed by lecturers in an EFL classroom observation of Islamic tertiary level of education in Indonesia. Qualitative methods, used to collect and analyze data gained from observation and interview. The result showed that the lecturer designed various activities in teaching Basic Listening in the EFL class, which they were set up in three stages: pre-listening, while-listening, and post-listening. The activities in the pre-listening were aimed at generating students’ interest, activating student’s prior knowledge, and trying to anticipate any difficult vocabularies. The while-listening stage is to invite students to be involved at listening through various physical movements, such as story telling, dialogue, listening to songs, and drama. The post-listening stage is to internalize what they have heard with other language skills and to check students’ comprehension.